2008
DOI: 10.1152/ajpheart.00305.2007
|View full text |Cite
|
Sign up to set email alerts
|

Novel anti-inflammatory mechanisms ofN-Acetyl-Ser-Asp-Lys-Pro in hypertension-induced target organ damage

Abstract: High blood pressure (HBP) is an important risk factor for cardiac, renal, and vascular dysfunction. Excess inflammation is the major pathogenic mechanism for HBPinduced target organ damage (TOD). N-acetyl-Ser-Asp-Lys-Pro (Ac-SDKP), a tetrapeptide specifically degraded by angiotensin converting enzyme (ACE), reduces inflammation, fibrosis, and TOD induced by HBP. Our hypothesis is that Ac-SDKP exerts its anti-inflammatory effects by inhibiting: 1) differentiation of bone marrow stem cells (BMSC) to macrophages,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
111
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 40 publications
(36 reference statements)
8
111
0
2
Order By: Relevance
“…Experiments in hypertensive rats have demonstrated that the naturally occurring tetra-peptide, N-acetyl-ser-asp-lys-pro (AcSDKP) reduces myocardial inflammation and prevents fibrosis mediated by Gal-3 [27,28]. In vitro experiments have also demonstrated inhibition of epithelial-to-mesenchymal transition in tissue culture [29].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in hypertensive rats have demonstrated that the naturally occurring tetra-peptide, N-acetyl-ser-asp-lys-pro (AcSDKP) reduces myocardial inflammation and prevents fibrosis mediated by Gal-3 [27,28]. In vitro experiments have also demonstrated inhibition of epithelial-to-mesenchymal transition in tissue culture [29].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with chronic HF, galectin-3 concentrations have been correlated with markers of extracellular matrix turnover, such as type III amino-terminal propeptide of procol- lagen (PIIINP) and matrix metalloproteinase 2 (MMP-2), implying a relationship between macrophage activation and collagen turnover (18 ). Intriguingly, N-acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP), a monocyte-derived antiinflammatory and antifibrotic peptide that is degraded by ACE, inhibits galectin-3 expression in the left ventricle and reduces galectin-3-induced macrophage activation and migration (19 ). In a rat model, intrapericardial infusion of Ac-SDKP mitigated many of the adverse effects of galectin-3, leading to reduced myocardial macrophage and mast cell density, decreased left ventricular collagen burden, and improved diastolic and systolic function (4 ).…”
Section: Galectin-3 and The Pathobiology Of Hfmentioning
confidence: 99%
“…It has shown that N-acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP) prevents inflammation, cell proliferation and fibrosis in the heart and kidney in a ANG II-induced hypertension model. They found that galectin-3 expression increased in left ventricular remodeling together with inflammatory markers IL-6, transforming growth factor-β (TGF-β), and TNF-α (22). Liu et al (23) recently showed that the co-infusion of Ac-SDKP with galectin-3 into the pericardial sac, inhibited fibrosis and inflammation and decreased cardiac dysfunction.…”
Section: Figure 1 Gross Appearances Of Control (A) and CD (B) Inducementioning
confidence: 99%